(untitled) (Innovative professional education, 2025)
The article highlights the process of developing and implementing a digital platform based on Google Workspace for the professional training of skilled workers in the mechanical engineering industry for the profession of «turner». The functional capabilities of the platform, its structure, and tools for organizing the learning process are described. The advantages of using digital technologies for distance learning, knowledge testing, interactive interaction, and educational content management are considered. The potential of the platform to improve the quality of professional training and meet the modern requirements of the industry is emphasized.